2018
DOI: 10.1155/2018/9131432
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis and Its Relationship with IL-10, IL-17, TGF-β, IFN-γ, IL 22, and IL-35

Abstract: Background We aimed in our study to research the role of new cytokines such as IL-35, IL-22, and IL-17 that may form a target for novel treatment approaches. Methods IL-10, IL-17, TGF-β, IFN-γ, IL-22, and IL-35 serum levels of allergic rhinitis (AR) patients were measured using ELISA method. Allergic sensitization was demonstrated by the skin prick test. Patients only with olive tree sensitivity were evaluated for seasonal AR (SAR). Patients only with mite sensitivity were included in the study for perennial A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 37 publications
6
56
0
1
Order By: Relevance
“…Our ndings are in agreement with the majority of clinical studies investigating IL-22 level in patients with allergic rhinitis and/ or allergic asthma and revealed that concentration of IL-22 in serum or plasma was higher in these patients than in healthy subjects (22)(23)(24)(25)(26)(27). Though, studies investigating local IL-22 level provided controversial results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our ndings are in agreement with the majority of clinical studies investigating IL-22 level in patients with allergic rhinitis and/ or allergic asthma and revealed that concentration of IL-22 in serum or plasma was higher in these patients than in healthy subjects (22)(23)(24)(25)(26)(27). Though, studies investigating local IL-22 level provided controversial results.…”
Section: Discussionsupporting
confidence: 88%
“…Some experimental studies showed that ovalbumin-challenged and IL-22-de cient mice had a low level of eosinophils in bronchoalveolar lavage and lung tissue and reduced leukocyte in ltration (31). In contrary, some other studies with animals reported that after ovalbumin stimulation IL-22-positive mice had a reduced number of eosinophils in the bronchoalveolar lavage when compared with IL-22-negative mice (28,29 (22). As mentioned before, these differences between studies could be determined by relatively small studies samples, different methods of IL-22 investigation and use of different tools for investigating severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed an elevated level of histamine, IgE, TNFand IL-1 in the serum of OVA-sensitized mice (Zhang, Li, Jia, & He, 2015). Other studies showed up-regulation of IL-10 and IFN-in serum in patients with AR compared with a normal population (Bayrak Degirmenci et al, 2018;Uguz, Sanlioglu, Yuzbey, Coskun, & Yegin, 2005). In order to further investigate whether OVA induction could increase the expression level of histamine and other OVA-specific inflammatory factors in vivo, blood specimens were collected on day 21, 24, 27 and 30 followed by ELISA assays, as illustrated in Figure 2.…”
Section: Up-regulation Of Histamine and Inflammatory Factors In Ova-smentioning
confidence: 93%
“…The overexpression of the IL-4, through genetic variation in regulatory regions and its physiological functions, gives it a preeminent role and responsibility for allergic inflammation. Perhaps this IL-4 role is part of a complex relationship between different ILs secreted by TH1 and TH2 and even the newly proposed cells, namely Th17 cells, which are a distinct subpopulation of CD4+ T cells that produce IL-17A, IL-17F, IL-22, TNF-α, and IL-21 [27]. Such a role can demonstrate the distinctive and enduring histological, pathophysiological, and clinical features of allergic inflammation, particularly of AR [10].…”
Section: Introductionmentioning
confidence: 97%